EFEKTIVITAS MEDIA VBL(VIDEO BASED LABORATORY) DALAM MENINGKATKAN PEMAHAMAN KONSEP FISIKA SISWA PADA TOPIK ELASTISITAS ZAT PADAT - Diana Puspa Ramadhanti; M. Nur M. Nur; Zulirfan Zulirfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to demonstrate the effectiveness of the Video- based laboratory (VBL) used in improving students' concepts of physics on the topic of elasticity of solid matter. This study in the background of practical activities in schools is still a major obstacle to learning activities. Low availability of pre-sight equipment and infrastructure, introduction time, inadequate laboratory equipment. For this reason, one solution that can be used to overcome the problem is by utilizing this evolving technology. One medium that can be used to help students assist in experimental activities is the Video Based Laboratory (VBL). This research is a research model from the revision of Karthwoll-Andersoon for cognitive level. The research was conducted on students of class XI 1 Teluk Kuantan, the number of students was 36 people. The actions were carried out in 2 groups, namely the experimental class with Video Based Laboratory (VBL) and the control group with lectures. After treatment, both classes will be given 15 cognitive tests. The data analysis used is descriptive data and inferential analysis. The results of the data in the field were tested with an independent T-test. The results showed that students in the experimental group were more effective than the control class with a significant data value of 0.008.Key words: Effectiveness, Video Based Laboratory, Cognitive learning results.